Micropolar flow over a black isothermal plate in the presence thermal radiation - Raptis, Anastasios (Zielona Góra: Uniwersytet Zielonogórski)
This study numerically investigates the effects of thermal radiation on the flow over a black isothermal plate for an optically thin gray micropolar fluid. The flowing medium absorbs and emits radiation, but scattering is not included. The computational results are discussed graphically for several selected flow parameters.
Keywords: micropolar fluid; thermal radiation; isothermal plate